TiAl3–Al porous by reactive synthesis with space holder method - Tiance Zhang (Elsevier, 2021)
It was difficult to get the advantages of the reactive synthesis with space holder method in preparing porous titanium aluminum materials. Explored a new method that can combine the advantages of both through TiAl3–Al porous fabricated at low titanium content. Moreover, the composition, structure and mechanical properties of different titanium content in this method were further studied. The reaction intensity of titanium and aluminum was effectively reduced by reducing the titanium content and sintering in the air. The pore wall morphology, the in-situ generated small pores were retained to a certain extent, and the product was only TiAl3. A series of complex changes caused by titanium content not only led to morphological changes and matrix transformation but also affected the mechanical properties. The change in microstructure and mechanical properties in different titanium content stages was very large.